Applying the marriage bond dissolution procedure in favor of faith in the Congregation for the Doctrine of the Faith in 2001-2006 - KAMIŃSKI , RAFAŁ (Prawo Kanoniczne, 2019)
Applying the marriage bond dissolution procedure in favor of faith in the Congregation for the Doctrine of the Faith in 2001-2006 The study analyzes material and procedural regulations issued in 2001 by the Congregation for the Doctrine of the Faith „Normae Potestas Ecclesiae de conficiendo processu pro solutione vinculi matrimonialis in favorem fidei”. These regulations apply to the cases that are not regulated in the Code of Canon Law in which it is possible to terminate a non-sacramental marriage by using the privilege of faith (privilegium fidei). The above situation applies to the marriages concluded by the parties, at least one of which is not baptized, if they were to be dissolved, in order to enter into a new sacramental relationship after being baptized by one of the parties and if it has not been consummated after being baptized by both of them. Such cases must be submitted to the Roman Bishop who, after the investigation performed by a competent bishop and then by the Congregation for the Doctrine of the Faith, judges according to his pastoral prudence whether the marriage bond is to be dissolved or not. The mentioned Dicastery of the Roman Curia, for proceeding in individual cases, issued procedural norms that have been modified over the years, taking into account the changing circumstances of life. The last of the documents from 2001 has been subjected to detailed analysis in this study. For this purpose both material and procedural aspects of the regulations contained in the document and the method of their application in the first years after their promulgation were taken into account. After presenting the assumptions and scope of application of applicable norms Potestas Ecclesiae, an analysis of the individual stages of the administrative procedure was carried out, both in the diocesan phase and at the level of the Holy See. In the last point of the publication there were contained the statistical data showing the practice of applying the norms Potestas Ecclesiae over the first few years after their entry into force.